Long-term safety of α-1 antitrypsin therapy in children and adolescents with Type 1 diabetes. (21st September 2018) - Brener, Avivit; Lebenthal, Yael; Interator, Hagar; Horesh, Orit; Leshem, Avital; Weintrob, Naomi; Loewenthal, Neta; Shalitin, Shlomit; Rachmiel, Marianna
Promising findings of α-1 antitrypsin (AAT) intervention in mice models of Type 1 diabetes (T1D) led researchers to investigate AAT as a therapeutic modality for β-cell preservation in recent-onset T1D patients. Our prospective, open-label Phase I/II extension study demonstrated that the administration of multiple repeated AAT infusions (up to 36) to AAT-sufficient pediatric T1D patients is safe and well-tolerated. Long-term surveillance of participants (up to 5 years) from diabetes onset revealed normal growth and pubertal progression through adolescence to attainment of full puberty and near adult height. No serious adverse events, clinical or laboratory abnormalities were reported. Given its safety profile, AAT may be an individualized-tailored innovative immunotherapy in AAT-sufficient pediatric patients with diverse immune-related medical conditions. ClinicalTrials.gov Identifier: NCT01661192